Characterising menotactic behaviours in movement data using hidden Markov models. Issue 10 (14th August 2021) - Togunov, Ron R.; Derocher, Andrew E.; Lunn, Nicholas J.; Auger‐Méthé, Marie
Abstract: Movement is the primary means by which animals obtain resources and avoid hazards. Most movement exhibits directional bias that is related to environmental features (defined as taxis when biased orientation is voluntary), such as the location of food patches, predators, ocean currents or wind. Numerous behaviours with directional bias can be characterised by maintaining orientation at an angle relative to the environmental stimuli ( menotaxis ), including navigation relative to sunlight or magnetic fields and energy‐conserving flight across wind. However, new methods are needed to flexibly classify and characterise such directional bias. We propose a biased correlated random walk model that can identify menotactic behaviours by predicting turning angle as a trade‐off between directional persistence and directional bias relative to environmental stimuli without making a priori assumptions about the angle of bias. We apply the model within the framework of a multi‐state hidden Markov model (HMM) and describe methods to remedy information loss associated with coarse environmental data to improve the classification and parameterisation of directional bias. Using simulation studies, we illustrate how our method more accurately classifies behavioural states compared to conventional correlated random walk HMMs that do not incorporate directional bias. We illustrate the application of these methods by identifying cross wind olfactory foraging and drifting behaviour mediated by wind‐driven sea ice drift in polar bears ( Ursus maritimus ) from movement data collected by satellite telemetry. The extensions we propose can be readily applied to movement data to identify and characterise behaviours with directional bias towards any angle, and open up new avenues to investigate more mechanistic relationships between animal movement and the environment. Résumé: Le déplacement est le moyen principal par lequel les animaux obtiennent des ressources et évitent les dangers. La plupart des déplacements présentent un biais directionnel lié à des caractéristiques environnementales telles que l'emplacement de sources de nourriture et de prédateurs, les courants marins ou le vent (appelé tactisme lorsque ce biais est volontaire). De nombreux comportements avec biais directionnel peuvent être caractérisés par le maintien d'une direction présentant un angle préférentiel par rapport aux stimuli environnementaux (i.e. ménotactisme ), par exemple, la navigation dirigée par la lumière du soleil ou les champs magnétiques, et le vol par vent de travers. Toutefois, de nouvelles méthodes sont nécessaires pour classifier et caractériser le biais directionnel de façon plus flexible. Nous proposons un modèle de marche aléatoire corrélée et biaisée pour identifier les comportements ménotactiques. Pour ce faire, le modèle décrit l'angle de déplacement comme un compromis entre la persistance directionnelle et le biais directionnel par rapport aux stimuli environnementaux, sans toutefois faire d'hypothèses a priori sur l'angle préférentiel. Nous utilisons la structure de modèle de Markov caché (MMC) à états multiples et décrivons des méthodes pour remédier à la perte d'informations liée à l'imprécision des données environnementales pour améliorer la classification et l'estimation du biais directionnel. À l'aide de simulations, nous illustrons comment notre méthode classifie les états comportementaux de manière plus précise que les MMC de marche aléatoire corrélée conventionnels qui n'incorporent pas de biais directionnels. Nous illustrons l'application de ces méthodes avec des données de suivi par satellite + d'ours polaires ( Ursus maritimus ). La méthode nous permet d'identifier les comportements de recherche olfactive au travers du vent et de dérive passive induite par le mouvement de la banquise poussée par le vent. Les modèles que nous proposons peuvent être facilement appliqués aux données de déplacements pour identifier et caractériser les comportements avec n'importe quel biais directionnel et ouvrent de nouvelles voies pour étudier de façon plus mécaniste les relations entre le déplacement des animaux et l'environnement.